Convergence of Qard and Ijarah Agreements Evidence of Gold Pawn Products from Bank Syariah Indonesia - Mujahidin, Mujahidin; Randi, Randi; Muin, Rahmawati; Sapira, Sapira (Al-'Adl, 2023)
The application of gold pawning in Islamic banks uses the concept of qardh and ijarah contracts with the guidance of Islamic economic law (sharia) with the provisions of the fatwa of the National Sharia Council (DSN) of the Indonesian Ulema Council (MUI). This study aims to determine the application of the Convergence of Qard and Ijarah Acts on Gold Pawn Products at Bank Syariah Palopo. The design in this research is field research that uses descriptive qualitative research methods with juridical analysis through observation, interviews. The results of this study reveal that the signing of qardh, rahn and ijarah contracts at Bank Syariah Mandiri Palopo is carried out separately to avoid gharar, jahalah and usury. Thus, qard products are not included in the hybrid contract category. The convergence of the gold pawn contract of Bank Syariah Mandiri Palopo City based on the research results is in accordance with the provisions of DSN fatwa No.25/DSN-MUI/III/2002 on rahn and DSN fatwa NO.26/ DSN -MUI/III/2002 on gold pawning. Thus, the convergence/integration of the qardh contract and ijarah contract in the gold pawn product at Bank Syariah Mandiri Palopo is appropriate because it is in accordance with and fulfils the DSN fatwa.